Evaluation of nursing interventions using minimally invasive assessments methods for patients in a persistent vegetative state. Issue 6 (4th April 2017) - Sato, Mitsue; Sugimoto, Masahiro; Yamaguchi, Kazuo; Kawaguchi, Takeshi
Abstract : Aim: This study aimed to evaluate the effects of nursing interventions using minimally invasive or non‐invasive methods conducive to frequent use in order to assess patients in a persistent vegetative state (PVS). Methods: We provided three nursing interventions—sitting the patient in an upright position, footbath care, and oral care—to PVS patients ( n  = 11) and elderly bedridden subjects with consciousness ( n  = 6) for 3 weeks in addition to ordinary nursing treatments. The Kohnan Score, plasma cortisol and adrenaline levels, General Well‐Being Schedule score, and facial expression assessments were used as evaluation methods. Results: The Kohnan Score of PVS patients declined significantly, indicating that the interventions increased patients' consciousness levels, but none of the other parameters showed significant change in either group. The change in Kohnan Score showed dependent trends for facial expression at baseline, cortisol change during the intervention, and the term of PVS. Conclusions: The data suggest three indices for predicting intervention efficacy in individuals and for assessing an intervention's contribution to quality of life improvement. Among the multiple evaluation methods, Konan Scores was the most effective. Ultimately, the three nursing interventions used in this study and Konan Score led to the optimization of nursing home care and rehabilitation for PVS patients.